Tourism destination social responsibility and the moderating role of self-congruity - Karatepe, Osman M.; Rezapouraghdam, Hamed; Hassannia, Raheleh; Kim, Taegoo Terry; Enea, Constana (Emerald Group Publishing Ltd, 2024)
Purpose - This paper investigates the interrelationships of destination social responsibility (DSR), emotional attachment, self-congruity, experiential satisfaction and environmentally responsible behavior (ERB).Design/methodology/approach - Using a sample of 294 visitors to the Guangzhou Zoo in China, this study tested the aforementioned relationships via structural equation modeling.Findings - Emotional attachment mediates the effect of DSR on experiential satisfaction, while emotional attachment and experiential satisfaction mediate the effect of DSR on ERB sequentially. Moreover, self-congruity moderates the relationship between DSR and emotional attachment.Practical implications - The management of zoos should use DSR communication strategies more proactively to make visitors become well-aware of their economic, philanthropic, environmental and social activities in the host community. This will result in many positive consequences, including visitors' ERBs.Originality/value - The study adds to the DSR literature by introducing multiple mediation mechanisms and paths that lead to visitors' ERBs.
Keywords: Destination social responsibility; Environmentally responsible behavior; Experiential satisfaction; Self-congruity; Zoo